Outcome of Laparoscopic Cholecystectomy as Ambulatory Surgery: Experience of 250 Cases - Ullah, Mahmud Ekram; Rahman, Md Mushfiqur; Rabbi, Hashim; Alam, Md Noor A; Maitra, Tapash Kumar (BIRDEM Medical Journal, 2019)
Background: Laparoscopic cholecystectomy has been performed as outpatient procedure for many years. Few studies have been conducted with primary focus on patient acceptance and preferences in terms of safety and satisfaction. We tried to explore its feasibility in otherwise healthy individuals undergoing laparoscopic cholecystectomy. Methods: Data from 250 patients with cholelithiasis who underwent laparoscopic cholecystectomy in BIRDEM General Hospital from April 2017 to June 2018 as ambulatory surgery (hospital stay d”23 Hours) with or without overnight stay were analyzed. Complications, admissions and readmissions, patient satisfaction and treatment expenditure were assessed. Results: Mean duration of hospital stay was 17.3 hours. Two patients had complications (deep port site infection) on 5th post-operative day after surgery. Only 2.4% patients required readmission while 9.2% patients had unplanned admission. Seventy six point four percent patients were highly satisfied with the procedure. Treatment cost was about 15% lower than routine inpatient operation. Conclusion: Laparoscopic cholecystectomy can be performed as an outpatient procedure with a low rate of complications and admissions/readmissions. Patient acceptance in terms of satisfaction is high. Birdem Med J 2019; 9(2): 157-161